THE IMPACT OF DIGITAL TRANSFORMATION AND E-COMMERCE ON THE INDIAN ART MARKET - Asrari, Masarrat; Jahan, Badar (International Journal of Research -GRANTHAALAYAH, 2025)
The paper discusses the Indian art market concerning e-commerce and digital transformation. The author attempts to present the interplay between technology and art business. There has been a sea change in the Indian art market post technological innovations and the rise of online art platforms. This expansion of online platforms has created new opportunities for artists and buyers in the form of artist studios, virtual exhibitions, and digital galleries. Significantly, the internet has become a mainstream venue for buying, selling, and investing in art, with people feeling more comfortable in the digital space. In this way, both technology and the art market are closely related. This study explores key aspects of the market, such as online auctions, new revenue streams and social media’s role in art promotion. Therefore, using secondary data and a descriptive research approach, the study presents an in-depth analysis of the Indian art market in relation to technological advancements. A thorough analysis of the opportunities and challenges presented by digitalisation concludes that while these advancements offer unparalleled benefits, they also introduce some serious risks. This new digital space also requires some modifications to preserve integrity and authenticity.